2005
DOI: 10.1128/aac.49.7.3080-3082.2005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Genotype-Phenotype Correlation among Macrolide-Resistant Streptococcus agalactiae Isolates

Abstract: Seventy-four erythromycin-resistant group B Streptococcus isolates were analyzed regarding their phenotypegenotype and phenotype-serotype correlation. Four different phenotypes were assessed, one of them for the first time. ermB and ermTR were the most frequent genotypes (80%). The most prevalent serotype III showed great phenotypic variability while serotype V was strongly associated only with two different phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
8
0
3
Order By: Relevance
“…It is particularly prudent to discover virulence factors in serotype V isolates, as they have often been reported to be resistant to antibiotics [12,26,[33][34][35]. It is particularly prudent to discover virulence factors in serotype V isolates, as they have often been reported to be resistant to antibiotics [12,26,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly prudent to discover virulence factors in serotype V isolates, as they have often been reported to be resistant to antibiotics [12,26,[33][34][35]. It is particularly prudent to discover virulence factors in serotype V isolates, as they have often been reported to be resistant to antibiotics [12,26,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The efflux pump is encoded by the mefA gene, whereas the acquisition of ermB and/or ermTR (erythromycin ribosome methylase) genes confers a ribosomal modification. erm genes are associated with macrolide-lincosamide-streptogramin B (MLS B ) resistance and can be expressed constitutively (cMLS B ) or upon induction (iMLS B ), although there is a heterogenic distribution of erm genes among these phenotypes [39]. Several studies have indicated how macrolide resistance might be acquired.…”
Section: Macrolide Resistancementioning
confidence: 99%
“…High rates of erythromycin and clindamycin resistance have, however, only been rarely reported: in one study testing 200 GBS isolates collected from vaginal/ rectal specimens [38], the resistance rate was 54% and 33%, respectively. Among erythromycin-resistant isolates, several studies have reported serotype V as the most frequent serotype [39][40][41][42][43].…”
Section: Macrolide-and Clindamycin-resistant Strainsmentioning
confidence: 99%
“…[4,5] To treat GBS infection, penicillin, ampicillin, and cefazolin are the drugs of choice; for patients allergic to penicillin or cephalosporins, vancomycin, macrolides (such as erythromycin, azithromycin, and clarithromycin), and lincosamides (clindamycin) may be used as the alternative drugs. [6][7][8][9] Vancomycin resistance has not been reported in GBS. However, in the USA, 12% of pregnant women are allergic to penicillin, and 25% and 7% of GBS isolates from these women are resistant to erythromycin and clindamycin, respectively.…”
Section: S Treptococcus Agalactiae (Group B Streptococcus Gbs)mentioning
confidence: 99%